2015
DOI: 10.1021/acsnano.5b01245
|View full text |Cite
|
Sign up to set email alerts
|

Universal Length Dependence of Rod-to-Seed Exciton Localization Efficiency in Type I and Quasi-Type II CdSe@CdS Nanorods

Abstract: A critical step involved in many applications of one-dimensional seeded CdSe@CdS nanorods, such as luminescent solar concentrators, optical gains, and photocatalysis, is the localization of excitons from the light-harvesting CdS nanorod antenna into the light-emitting CdSe quantum dot seed. We report that the rod-to-seed exciton localization efficiency decreases with the rod length but is independent of band alignment between the CdSe seed and CdS rod. This universal dependence can be well modeled by the compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
174
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(194 citation statements)
references
References 73 publications
19
174
1
Order By: Relevance
“…There are two different regions: 1) the percentage of the third component is at a maximum and decreases with increasing wavelength between 480 and 550 nm, and 2) the percentages of the three components are almost constant from 550 to 710 nm. [50][51][52][53][54] To investigate further the piezochromic effect in the Ti 3 C 2 MQDs, we investigated the influence of applied pressure on their luminescence. The ESA signal of the surface state with a lower energy level lies at shorter wavelengths near 505 nm, but the signal of the core state occurs at longer wavelengths at 600 nm.…”
Section: Resultsmentioning
confidence: 99%
“…There are two different regions: 1) the percentage of the third component is at a maximum and decreases with increasing wavelength between 480 and 550 nm, and 2) the percentages of the three components are almost constant from 550 to 710 nm. [50][51][52][53][54] To investigate further the piezochromic effect in the Ti 3 C 2 MQDs, we investigated the influence of applied pressure on their luminescence. The ESA signal of the surface state with a lower energy level lies at shorter wavelengths near 505 nm, but the signal of the core state occurs at longer wavelengths at 600 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the low ΦPL values at this short excitation wavelength are mainly caused by a decreased shell-to-core exciton localization efficiency, resulting from the competition between exciton diffusion through the elongated CdS shell to the CdSe core and exciton trapping within the shell. 28 However, the τPL values of the longest QDQRs (A-100 and B-100) at 450 nm excitation are again slightly shorter compared to the τPL of the 50 nm QDQRs (A-50 and B-50). This is attributed to an increased number of defect states for the longer rods, as the probability of defect states increases with the shell length of the QDQRs.…”
Section: Instrumentationmentioning
confidence: 92%
“…Within the last decades, the question if QDs and QDQRs show an excitation wavelength (λexc) dependence of ΦPL, 21 has been addressed by several groups with controversial results. [25][26][27][28] For example, a strong λexc dependence of ΦPL was observed by Hoheisel et al for a series of CdSe QDs with radii from 0.9 nm up to 2.6 nm including a considerably diminished PL efficiency for excitation within the absorption continuum, i.e., to higher excited states relative to the band edge. 25 Measurements of ΦPL of CdSe and CdSe/ZnS QDs dispersed in toluene from Hoy et al revealed also the highest ΦPL for excitation just above the band gap.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Experiments on CdSe/CdS dot-in-rod structures have also been interpreted to show long-lived exciton localization in the CdS shell. 20,23,29 Mechanism and magnitude of electron-phonon coupling Both the bulk band offsets and a wealth of experimental evidence indicate that in CdSe/CdS core/shell QDs, the lowest excitonic transition involves a hole that is largely localized to the CdSe core and an electron that is fairly delocalized throughout the core and shell ("type I ½" or "quasi-type II"). Compared with pure CdSe QDs, where there is only a small amount of spatial separation between electron and hole, the lowest excitonic state of the core/shell structures should involve considerably larger internal electric fields and, therefore, stronger coupling to 15 polar optical phonons through the Fröhlich mechanism.…”
Section: Figure 7 Experimental (Black) and Calculated (Red) Frequencmentioning
confidence: 99%